Lies in Disguise - A Theoretical Analysis of Cheating - Martin Dufwenberg Jr.; Martin Dufwenberg (Center for Economic Studies and ifo Institute (CESifo), 2016)
We perform a (psychological) game-theoretic analysis of cheating in the setting proposed by Fischbacher & Föllmi-Heusi (2013). The key assumption, which we refer to as perceived cheating aversion, is that the decision maker derives disutility in proportion to the amount in which he is perceived to cheat. A particular equilibrium captures the stylized facts from many experiments (in particular the co-presence of selfish, honest, and partial-lie choices) well.
Keywords: C72; D03; D82; D83; H26; 330; cheating; lying; costs; audience; perceived cheating aversion